Expression of IL32 and IL33 Genes in Tuberculosis Patients - Qasim Dhumad, Bushra (Journal for Research in Applied Sciences and Biotechnology, 2024)
In the present case-control study, blood specimens were obtained from (60) patients infected with TB from TB center in Baghdad city, and from (60) healthy persons as a control group during the period from January 2023 to December 2023. Results of demographic picture showed that the distribution of infections in males was 31(51.7%) compared to the control group 3(51.7%) and in females was 29 (48.3%) compared to the control group 29 (48.3%). The infection distribution according to age revealed that the highest infection rate was shown to be within the age group (<20 -29), followed by (30-39) then (40-50) years, which matched with the control group (<20 -29). According to residency, there were no significant differences between rural and urban residents. Mean ±Std anti TB IgM antibodies was (2.40±1.44) in comparison with controls (0.08±0.17), with highly significant difference (P<0.01). Also, Mean ±Std anti TB IgG antibodies was (1.42±0.59) in comparison to controls (0.11±0.21), with highly a significant differences P< 0.01. Mean±Std IL-33 was (20.38±6.53) in comparison to the controls (2.28±2.48), with highly significant differences P<0.01. Also, mean ±Std IL-32 was (10.61±2.24) in comparison to the control group (1.89±2.043) with highly significant differences P< 0.01. Expression of IL32 in TB patients showed positive reaction and it was highly affected in patients with TB compared to the control group, while expression of IL33 in TB patients showed positive reaction and was highly affected in patients with TB compared to the control group.